Visual ethnography of the Aneuk Jamee bridal chamber as an effort to preserve cultural products in Tapak Tuan, Aceh Province - Lindawati, Lindawati; Bakhir , Norfarizah Mohd; Ismawan, Ismawan; Ramdiana , Ramdiana (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2024)
This article investigates the bridal chamber aisle of the Aneuk Jamee tribe in Tapaktuan District which is rarely used by the community. This aisle is one of the visual cultural products that need to be preserved. The research uses a visual ethnography approach. Visual ethnography provides a new way of revealing, describing, and analyzing cultural products and human experiences. Data were obtained through interviews, observation, and documentation. Data analysis was carried out by visual ethnography analysis. The results of the study found that, bridal room aisles are rarely used by the Aneuk Jamee tribe due to the times where many aisle businesses offer more modern bridal room decorations and the lack of government role in maintaining the use of bridal room aisles. The visual form of the bridal room aisle has its own characteristics and meaning. With this article, it is hoped that people can find out the parts and meanings contained in the bridal aisle of the Aneuk Jamee tribe. These meanings become the basis for contemplating actions to maintain the continuity of tradition in the face of growing innovation.